Cover. (27th September 2018) - Nagamatsu, Takeshi; Fujii, Tatsuya; Schust, Danny J.; Tsuchiya, Naoko; Tokita, Yohei; Hoya, Mari; Akiba, Naoya; Iriyama, Takayuki; Kawana, Kei; Osuga, Yutaka; Fujii, Tomoyuki
Abstract : The cover image, by Takeshi Nagamatsu et al., is based on the Original Article Tokishakuyaku‐san, a Japanese herbal medicine mitigates iNKT cell mediated pregnancy loss in mice, DOI:10.1111/aji.13021 .